Desain Media Pembelajaran Interaktif Terintegrasi Problem Based Learning Topik Pencemaran Lingkungan - Wali Saryono; Sigit Sujatmika; Astuti Wijayanti (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
Abstract: Development research (design research) with the 4D model (define, design, develop, disseminate) aims to 1) develop interactive learning media based on Problem Based Learning (PBL) for seventh grade junior high school students, 2) find out the feasibility of interactive learning based media PBL for grade VII junior high school students. Research is limited to the develop stage. Data collection techniques use assessment instruments for several experts. The data analysis technique uses descriptive qualitative and quantitative analysis based on the ideal evaluation category. Based on the results of the assessment of media experts obtained an average score of 64, with a percentage of ideals of 80%, including both categories. The results of the assessment of material experts obtained an average score of 59, with an ideal percentage of 81.94%, including the excellent category. Peer reviewer assessment results obtained an average score of 72, with a percentage of ideals of 90%, including the excellent category. The results of the science teacher assessment obtained an average score of 117, with an ideal percentage of 81.38%, including the excellent category. The results of the assessment of student responses obtained an average score of 68.55, with an ideal percentage of 81.68%, including the excellent category. It can be concluded that the interactive learning media developed is very feasible to use in learning. Keywords: Interactive Learning Media, Problem Based Learning